A proposal to sequence the genome of a garter snake (Thamnophis sirtalis). Issue 2 (March 2011) - Castoe, Todd; Bronikowski, Anne; Brodie, Edmund; Edwards, Scott; Pfrender, Michael; Shapiro, Michael; Pollock, David; Warren, Wesley
Abstract Here we develop an argument in support of sequencing a garter snake (Thamnophis sirtalis ) genome, and outline a plan to accomplish this. This snake is a common, widespread, nonvenomous North American species that has served as a model for diverse studies in evolutionary biology, physiology, genomics, behavior and coevolution. The anole lizard is currently the only genome sequence available for a non-avian reptile. Thus, the garter snake at this time would be the first available snake genome sequence and as such would provide much needed comparative representation of non-avian reptilian genomes, and would also allow critical new insights for vertebrate comparative genomic studies. We outline the major areas of discovery that the availability of the garter snake genome would enable, and describe a plan for whole-genome sequencing.